40Ar-39Ar ages of Antarctic meteorites: Y-74191, Y-75258, Y-7308, Y-74450 and ALH-765 - Kaneoka, Ichiro (1981)
P(論文) The ^<40>(Ar)-^<39>(Ar) ages have been determined for two chondrites (Y-74191,Y-75258), one howardite (Y-7308) and two eucrites (Y-74450,ALH-765) from Antarctica. Y-74191 (L3) shows a disturbed age spectrum with a maximum apparent age of 4506±31 Ma in the intermediate temperature fraction. Y-75258 (LL6) shows a plateau age of 4377±14 Ma at higher temperatures except for the highest temperature fraction. A howardite Y-7308 has an inversed age spectrum, but the intermediate temperature fractions indicate a plateau-like age of 4480±30 Ma. The apparent very old age at the lowest temperature might have been caused either by the effect of atmospheric contamination to the sample or by the redistribution of radiogenic ^<40>(Ar) in the sample. One eucrite Y-74450 shows a plateau age of 4012±22 Ma, indicating a later thermal event on the parent body of the meteorite. The other eucrite ALH-765 indicates a gradual increase in the apparent ^<40>(Ar)-^<39>(Ar) ages with increasing degassing temperature, but even the highest temperature fraction shows an age of about 3700 Ma. The present results together with those of reported ^<40>(Ar)-^<39>(Ar) and K-Ar ages suggest that meteorites found in Antarctica represent thermal histories very different from one another. departmental bulletin paper